2014
DOI: 10.1097/sla.0000000000000954
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Double-Blinded Randomized Controlled Trial of Standard Abdominal Wound Edge Protection With Surgical Dressings Versus Coverage With a Sterile Circular Polyethylene Drape for Prevention of Surgical Site Infections

Abstract: Our trial shows that CWEPs are effective at reducing the incidence of SSIs in elective and clean or clean-contaminated open abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 33 publications
4
75
0
2
Order By: Relevance
“…The German double-blinded, randomized, controlled trial, BaFO, demonstrated that the single-ring WEP significantly reduced the incidence of SSI [9]. In their study, the incidence of SSI in patients with and without a WEP was 17.7 and 25.2% respectively ( p = 0.026).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The German double-blinded, randomized, controlled trial, BaFO, demonstrated that the single-ring WEP significantly reduced the incidence of SSI [9]. In their study, the incidence of SSI in patients with and without a WEP was 17.7 and 25.2% respectively ( p = 0.026).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies showed the usefulness of WEPs, they included not only colorectal but also other types of gastrointestinal surgeries [8, 9, 11]. At the same time, racial differences such as BMI should be taken into consideration to interpret the results of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wounds were evaluated daily by a surgeon during the postoperative course until discharge. Postoperative SSI were classified according to the CDC guidelines [5,20]. All patients gave written informed consent and the project was approved by the local Ethics committee of the Technische Universit€ at München, Munich, Germany.…”
Section: Patients and Tissue Samplingmentioning
confidence: 99%
“…Имеют значение, но не оказывают статистически значимого влияния на риск развития послеоперационных осложнений: наложение превентивной стомы; возраст больного; наличие сопутствующей патологии; уровень пересечения нижней брыжеечной артерии; дополнительная мобилизация вышележащих отделов толстой кишки; тип формирования анастомоза; гистологический тип новообразования и стадия процесса [10,11].…”
unclassified